An Econometric Analysis of the Mental-Health Effects of Major Events in the Life of Elderly Individuals - Maarten Lindeboom; France Portrait; Gerard J. van den Berg (Institute for the Study of Labor (IZA), 2001)
Major events in the life of an elderly individual, such as retirement, a significant decrease in income, death of the spouse, disability, and a move to a nursing home, may affect the mental health status of the individual. For example, the individual may enter a prolonged depression. We investigate this using unique longitudinal panel data that track labor market behavior, health status, and major life events, over time. To deal with endogenous aspects of these events we apply fixed effects estimation methods. We find some strikingly large effects of certain events on the occurrence of depression. We show that the results are of importance for the design of health care and labor market policy towards the elderly.
Keywords: C5; I1; 330; Death; retirement; income loss; disease; depression; health indicators; widowhood; care; panel data; endogeneity; fixed effects; Psychische Störung; Alte Menschen; Ökonometrisches Modell; Niederlande